Effect of organic growing media and crop geometry on growth and yield of capsicum var. California wonder under protected condition in North West Himalayas - Roy, Sumita; Kumar, Narendra; Singh, DK; Srivastava, AK (Vegetable Science, 2011)
An experiment was conducted inside polyhouse during 2008 and 2009 to study the effect of organic growing media and plant spacing on growth and yield of capsicum variety California Wonder in the mid hills of north western Himalayas. The media consisting of Soil : Sand : FYM : Vermicompost (1 : 1 : 0.5 : 0.5) proved to be statistically superior over rest of the combinations for almost all the aspects under investigation. All the attributes were better or at par when the depth of the media was kept at lesser depth (15cm) and the plants at wider spacing (50x50cm). Therefore it can be inferred that incorporation of vermicompost and FYM led to the better soil properties and nutrient supply to plants, whereas appropriate crop geometry created suitable micro environment for proper plant competition. Better performance of the plants in lesser depth of media in turn made the cultivation economical for the growers.